2014
DOI: 10.1063/1.4864742
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization dynamics of cobalt grown on graphene

Abstract: Ferromagnetic resonance (FMR) spin pumping is a rapidly growing field which has demonstrated promising results in a variety of material systems. This technique utilizes the resonant precession of magnetization in a ferromagnet to inject spin into an adjacent non-magnetic material. Spin pumping into graphene is attractive on account of its exceptional spin transport properties. This article reports on FMR characterization of cobalt grown on CVD graphene and examines the validity of linewidth broadening as an in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Unfortunately, no independent measurements of M s or H ⊥ k were reported in [30] or [14]. Further evidence of the need for caution comes from a study of 14 nm thick Co films deposited by evaporation onto Gr/SiO 2 and SiO 2 substrates [15]. Careful characterization by FMR, magnetometry, magnetic force microscopy, and Kerr microscopy revealed such clear magnetic differences between the samples that the authors, commendably, declined to draw any conclusions about spin pumping into Gr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, no independent measurements of M s or H ⊥ k were reported in [30] or [14]. Further evidence of the need for caution comes from a study of 14 nm thick Co films deposited by evaporation onto Gr/SiO 2 and SiO 2 substrates [15]. Careful characterization by FMR, magnetometry, magnetic force microscopy, and Kerr microscopy revealed such clear magnetic differences between the samples that the authors, commendably, declined to draw any conclusions about spin pumping into Gr.…”
Section: Discussionmentioning
confidence: 99%
“…We discuss these limitations in detail, drawing on our results and on other recently published work [15]. Finally, we attribute the suppression of spin pumping in Py/Gr/Cu to the large contact resistance of the Gr/Cu interface [16].…”
Section: Introductionmentioning
confidence: 90%
“…Estimates of the spin-mixing conductance obtained from the broadening of the FMR peaks resulted in surprisingly high values (e.g.,   g 5.2610 19 m -2 from Py/Gr = Py/Gr -Py = 110 -2 ), comparable to systems with high spin-orbit coupling 7 (such as heavy metals Pt and Pd). In addition, the direct deposition of the ferromagnetic Permalloy (Py) film on top of the graphene layer could cause magneto-structural 16 changes in the Py surface and a subsequent increase in straight fields altering the spin dynamics and accumulation in the semiconductor 17 , responsible for the observed change in damping when comparing with films without graphene, i.e., deposited on the bare wafer. A direct measurement of the spin Hall angle in FM/Gr interfaces has not been reported yet.…”
Section: Singapore Singapore 117456mentioning
confidence: 99%
“…Most likely, the observed FMR broadening is due to changes in the magnetic response of the Py due to surface changes induced by the graphene, such as an enhancement of two-magnon scattering processes. It has been recently shown that the deposition of Co films on graphene results in magnetic variations and enhanced magnetic coercivity 16 . In our case, for example, we observe a slight change (<10%) in the magnetization saturation when graphene is present (not shown here).…”
Section: Singapore Singapore 117456mentioning
confidence: 99%
“…4(c)). Growth of Co on graphene can result in enhanced grain and domain formation of Co due to graphene's high surface diffusion 18,24,25 , and domains could be pinned above the graphene by these grain boundaries.…”
mentioning
confidence: 99%